2014
DOI: 10.2478/eko-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of afforestation of agricultural soils and tree species composition on soil physical characteristics changes

Abstract: vopravil J., Podrázský v., Khel t., holubík o., vacek s.: Effect of afforestation of agricultural soils and tree species composition on soil physical characteristics changes. Ekológia (Bratislava), vol. 33, no. 1, p. 67-80, 2014. This paper deals with the evaluation of the effect of afforestation of previously arable land to soil characteristics changes. one of the main aims was to evaluate the effects of each forest species on the soil structure quality after afforestation. soil samples were taken at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Thus, arable lands in this territory after conversing of forest do not have suitable BD. Also, the hypotheses that BD will decrease after afforestation is not supported by our results (recovered AL), and contradicts the conclusions from other studies [38,39], but agrees with the work of Vopravil et al [40] which found that previously arable horizon characteristics can persist for a long time. There is also probability that in this study, the abandonment age is too short to see the gradual restoration of BD after afforestation which is shown in [41].…”
Section: Discussionsupporting
confidence: 75%
“…Thus, arable lands in this territory after conversing of forest do not have suitable BD. Also, the hypotheses that BD will decrease after afforestation is not supported by our results (recovered AL), and contradicts the conclusions from other studies [38,39], but agrees with the work of Vopravil et al [40] which found that previously arable horizon characteristics can persist for a long time. There is also probability that in this study, the abandonment age is too short to see the gradual restoration of BD after afforestation which is shown in [41].…”
Section: Discussionsupporting
confidence: 75%
“…Different factors explaining variation of forest herbaceous layer were studied previously, for example, soil properties and overstorey structure (Zhukov et al, 2019). On the other hand, biotic factors as vegetation type and presence/absence of some groups of organisms are also important for soil processes and soil characteristics changes (Vopravil et al, 2014). The results of our study also explained the reasons of observed variable scale variation of this layer in different forest communities.…”
Section: Discussionsupporting
confidence: 63%
“…The affinity and dependence of different plant species on different mycorrhizal fungi are very different. Therefore, in the process of afforestation, the best combination of tree species and mycorrhizal fungi should be screened firstly (Vopravil et al 2014). Therefore, the C. geophilum strains are suitable for forestation and afforestation, which will have a profound impact on the construction of plantation in China, provide a scientific basis for the theory and practice of vegetation restoration, and has a strong promotion and application value.…”
Section: Resultsmentioning
confidence: 99%